Linum grandiflorum primary assembly and gene annotation - Fracassetti, Marco; Zervakis, Panagiotis; Postel, Zoe; Losvik, Aleksandra; Soler, Lucile; Proux‐Wéra, Estelle; Bunikis, Ignas; Churcher, Allison; Slotte, Tanja (Stockholm University, 2026)
This dataset contains the fasta file (Lgrand_primary_v1.fasta.gz) and the gene annotation (Lgrand_primary_v1_genes.gff.gz) of Linum grandiflorum primary assembly.

The annotated assembly has been deposited in the European Nucleotide Archive, ENA (Project PRJEB87189) but it is incomplete, it contains only three contigs.

The genome assembly is based on PacBio HiFi and Hi-C data using Hifiasm (https://github.com/chhylp123/hifiasm).

The gene annotation has been done with MAKER (https://www.yandell-lab.org/software/maker.html) and manually curated by NBIS.

This dataset is associated with this article: Zervakis, P. I., Postel, Z., Losvik, A., Fracassetti, M., Solér, L., Proux‐Wéra, E., ... & Slotte, T. (2025). Genomic studies in Linum shed light on the evolution of the distyly supergene and the molecular basis of convergent floral evolution. New Phytologist, 247(6), 2964-2981.
Keywords: Evolutionary ecology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi